The Global Findex Database 2014 : Measuring Financial Inclusion around the World - Demirguc-Kunt, Asli; Klapper, Leora; Singer, Dorothe; Van Oudheusden, Peter (World Bank, Washington, DC, 2015)
The Global Financial Inclusion (Global Findex) database, launched by the World Bank in 2011, provides comparable indicators showing how people around the world save, borrow, make payments, and manage risk. The 2014 edition of the database reveals that 62 percent of adults worldwide have an account at a bank or another type of financial institution or with a mobile money provider. Between 2011 and 2014, 700 million adults became account holders while the number of those without an account—the unbanked—dropped by 20 percent to 2 billion. What drove this increase in account ownership? A growth in account penetration of 13 percentage points in developing economies and innovations in technology—particularly mobile money, which is helping to rapidly expand access to financial services in Sub-Saharan Africa. Along with these gains, the data also show that big opportunities remain to increase financial inclusion, especially among women and poor people. Governments and the private sector can play a pivotal role by shifting the payment of wages and government transfers from cash into accounts. There are also large opportunities to spur greater use of accounts, allowing those who already have one to benefit more fully from financial inclusion. In developing economies 1.3 billion adults with an account pay utility bills in cash, and more than half a billion pay school fees in cash. Digitizing payments like these would enable account holders to make the payments in a way that is easier, more affordable, and more secure.